Resource use during systematic review production varies widely: a scoping review - Nussbaumer-Streit, Barbara; Ellen, Moriah; Klerings, Irma; Sfetcu, Raluca; Riva, Nicoletta; Mahmić-Kaknjo, Mersiha; Poulentzas, Georgios; Martinez, Pablo Gonzalez; Baladia, Eduard; Ziganshina, Liliya Eugenevna; Marqués, María E.; Aguilar, L.; et al. (My University, 2021)
Objective We aimed to map the resource use during systematic review (SR) production and reasons why steps of the SR production are resource intensive to discover where the largest gain in improving efficiency might be possible. Study design and setting We conducted a scoping review. An information specialist searched multiple databases (e.g., Ovid MEDLINE, Scopus) and implemented citation-based and grey literature searching. We employed dual and independent screenings of records at the title/abstract and full-text levels and data extraction. Results We included 34 studies. Thirty-two reported on the resource use—mostly time; four described reasons why steps of the review process are resource intensive. Study selection, data extraction, and critical appraisal seem to be very resource intensive, while protocol development, literature search, or study retrieval take less time. Project management and administration required a large proportion of SR production time. Lack of experience, domain knowledge, use of collaborative and SR-tailored software, and good communication and management can be reasons why SR steps are resource intensive. Conclusion Resource use during SR production varies widely. Areas with the largest resource use are administration and project management, study selection, data extraction, and critical appraisal of studies.
Keywords: Evidence synthesis; Time; Personnel; Costs; Resources; Efficient; Russian Federation